Cellular automata : 12th International Conference on Cellular Automata for Research and Industry, ACRI 2016. Fez, Morocco, September 5-8, 2016, proceedings /: 12th International Conference on Cellular Automata for Research and Industry, ACRI 2016. Fez, Morocco, September 5-8, 2016, proceedings. (2016) - Unknown
No abstract available